Dana Program Pengembangan Daerah Pemilihan (Dana Aspirasi) DPR RI: Tinjauan Kedudukan Dan Kebutuhan Dalam Perspektif Hukum Tata Negara - mei susanto (Fakultas Hukum Universitas Islam Indonesia, 2017)
The aspirations fund of the House of Representative to be one hot issue discussed publicly, especially with regard to the right of the House budget. Problems posed, first, how the position of the aspirations funds of the House associated with the function of the House Budget? Second, what the aspirations funds of the House become a necessity in response to House obligation in fulfilling the aspirations of the people? This research is doctrinal, using primary and secondary legal materials, in the form of some legislation, literature and research results which are relevant to the object of research. The approach used in this study is the approach of legislation, comparison, and conceptual. The study concluded, first, the aspiration funds of the House is not the function of budget of the House, because the House should function gives approval and not received an allocation of a specific budget as an executive. Secondly, the aspirations fund of the House is not an answer to the need to meet the aspirations of the people, can even cause negative culture that is pork barrel politics.